2005
DOI: 10.1128/mcb.25.9.3737-3751.2005
|View full text |Cite
|
Sign up to set email alerts
|

Direct p53 Transcriptional Repression: In Vivo Analysis of CCAAT-Containing G2/M Promoters

Abstract: Promoters and enhancers are a combinatorial puzzle of DNA elements recognized by sequence-specific regulators that act in a chromatin context. The CCAAT box is a common promoter element, usually positioned in either orientation between Ϫ60 and Ϫ100.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
228
3
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(250 citation statements)
references
References 65 publications
17
228
3
2
Order By: Relevance
“…Previous reports showed that HDAC4 is a key mediator of p53-dependent cancer cell growth arrest in response to DNA damage (Kao et al, 2003;Imbriano et al, 2005;Basile et al, 2006). Here, we demonstrated that HDAC4 represses p21 WAF1/Cip1 expression in proliferating unstressed cancer cells through a p53-independent mechanism.…”
Section: Hdac4 Represses P21waf1/cip1 Expression In Human Cancer Cellsupporting
confidence: 60%
“…Previous reports showed that HDAC4 is a key mediator of p53-dependent cancer cell growth arrest in response to DNA damage (Kao et al, 2003;Imbriano et al, 2005;Basile et al, 2006). Here, we demonstrated that HDAC4 represses p21 WAF1/Cip1 expression in proliferating unstressed cancer cells through a p53-independent mechanism.…”
Section: Hdac4 Represses P21waf1/cip1 Expression In Human Cancer Cellsupporting
confidence: 60%
“…Interestingly, unlike the mechanisms discussed earlier, transactivation by the mutp53-NF-Y complex does not require the N terminus of mutp53, implying that this activity of mutp53 utilizes other domains of the protein. In support of this, wtp53 interacts with NF-Y, p300 and HDAC1 through its C-terminal domain (Imbriano et al, 2005).…”
Section: Mutp53: Role Of Residual Wtp53 Activity?mentioning
confidence: 81%
“…The protein p53 interacts with Sp1 and NF-Y transcription factor (Imbriano et al, 2005;Koutsodontis et al, 2005). This interaction either reduces the ability of these factors to bind to DNA, resulting in insufficient (Imbriano et al, 2005;Jin et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…This interaction either reduces the ability of these factors to bind to DNA, resulting in insufficient (Imbriano et al, 2005;Jin et al, 2008). To elucidate the mechanism by which p53 downregulates Cdc25B, we performed chromatin immunoprecipitation (ChIP) analyses.…”
Section: Resultsmentioning
confidence: 99%